On the trail of Neolithic mice and men towards Transcaucasia: zooarchaeological clues from Nakhchivan (Azerbaijan). (10th January 2013) - Cucchi, Thomas; Kovács, Zsófia Eszter; Berthon, Rémi; Orth, Annie; Bonhomme, François; Evin, Allowen; Siahsarvie, Roohollah; Darvish, Jamshid; Bakhshaliyev, Veli; Marro, Catherine
Abstract : Transcaucasia comprises a key region for understanding the history of both the hybrid zone between house mouse lineages and the dispersal of the Neolithic way of life outside its Near Eastern cradle. The opportunity to document the colonization history of both men and mice in Transcaucasia was made possible by the discovery of mouse remains accumulated in pits from a 6000‐year‐old farming village in the Nakhchivan (Autonomous Republic of Nakhchivan, Azerbaijan). The present study investigated their taxonomy and most likely dispersal path through the identification of the Mus lineage to which they might belong using a geometric morphometric approach of dental traits distances between archaeological and modern populations of the different Mus lineages of South‐West Asia. We demonstrate that the mouse remains trapped in the deep storage pits of the dwelling belong to the Mus musculus domesticus from the Near East, with dental shapes similar to current populations in Northern Syria. These results strongly suggest that the domesticus lineage was dispersed into Transcaucasia from the upper Euphrates valley by Neolithic migration, some time between the 7th and 5th millennium BC, providing substantial evidence to back up the scenario featuring near‐eastern stimuli in the emergence of agriculture in the South Caucasus. The domesticus mitochondrial DNA signature of the current house mouse in the same location 5000 years later, as well as their turnover towards a subspecies musculus/castaneus phenotype, suggests that early domesticus colonizers hybridized with a later musculus (and maybe castaneus ) dispersal originating from south of the Caspian Sea and/or Northern Caucasia. © 2013 The Linnean Society of London